A REVIEW OF DIY'S DECENTRALIZATION OF THE URBAN SPRAWL PHENOMENON IN THE YOGYAKARTA METROPOLITAN AREA (KARTAMANTUL) - Alvianti, Vivian; Fathurrahman, Fathurrahman (STKIP PGRI Situbondo, 2024)
Decentralization in Indonesia has led to a shift in responsibilities from the central government to the regions. This has been observed in the distribution of jobs and population across metropolitan areas, such as in the Yogyakarta Metropolitan Area (Kartamantul). Kartamantul is a secondary metropolitan area in Indonesia where local governments have taken the initiative to jointly form a Joint Secretariat. The development of Kartamantul has expanded into the peripheral areas, as evidenced by changes in land use. This article examines the impact of decentralization by the Government of the Special Region of Yogyakarta on the phenomenon of urban sprawl in the Kartamantul Region. The analytical method used is descriptive analysis, with secondary data collection from previous research on decentralization and urban sprawl in Yogyakarta. The results of the analysis identify the characteristics of urban sprawl in Kartamantul based on three aspects: land use change, population growth, and economic growth. By 2017, there had been changes in non-built-up land use in the peri-urban areas of Yogyakarta, accompanied by population growth and economic expansion. The Joint Secretariat of Kartamantul has come up with solutions to address the urban sprawl phenomenon, such as the addition of Trans-Jogja routes reaching Bantul and Sleman regencies, as well as collaborative management of the Piyungan Landfill and Sewon WWTP. The conclusion of this research is that cooperation among regional governments through the Joint Secretariat of Kartamantul is an effective grassroots initiative. However, there is a need for the Joint Secretariat to be involved in spatial planning due to the complex development challenges in Kartamantul.